The impact of post-pulmonary embolism syndrome and its possible determinants. Issue 171 (November 2018) - Tavoly, Mazdak; Wik, Hilde S.; Sirnes, Per-Anton; Jelsness-Jørgensen, Lars-Petter; Ghanima, Josef P.; Klok, Frederikus A.; Sandset, Per-Morten; Ghanima, Waleed
Abstract: Introduction: Recent studies suggest that up to 50% of patients surviving pulmonary embolism (PE) may suffer from post-PE syndrome, which is defined by persistent dyspnea, impaired exercise capacity and/or decreased health-related quality of life (HRQoL). The possible determinants of post-PE syndrome are however not fully established. Aims: To describe the differences between dyspneic and non-dyspneic PE-patients and to explore determinants of dyspnea, 6-min walking test (6MWT) and HRQoL. Material and methods: In this cross-sectional study, consecutive patients diagnosed with PE between 2002 and 2011 at Østfold Hospital, Norway were identified from hospital registries. Patients were scheduled for clinical examination and a 6MWT. Dyspnea was assessed by the New York Heart Association (NYHA) classification. HRQoL was assessed with PEmb-QoL questionnaire. PE severity was assessed with PESI score, mean bilateral proximal extent of the clot and right-/left ventricle-ratio (RV/LV-ratio). Results: 203 patients participated in this study, of which 96 patients reported dyspnea (47%). Median time from diagnosis was 3.6 years (IQR 1.9–6.5). Patients without dyspnea performed better on 6MWT (488 m vs 413 m, p < 0.005) and had better HRQoL results (p < 0.005). None of the variables we examined, including Charlson comorbidity index, was independently associated with dyspnea. However, higher RV/LV ratio at diagnosis was significantly associated with reduced 6MWT at follow-up. Further, ongoing anticoagulation and unemployment were independently associated with impaired HRQoL. Conclusions: PE-survivors complaining of dyspnea suffer from impaired HRQoL and reduced exercise capacity. Although PE-severity factors were associated with reduced exercise capacity, none of the examined factors were found to be independent determinants of dyspnea. Highlights: Persistent dyspnea, reduced 6MWT and impaired HRQoL are independently associated. Impaired post-PE recovery cannot simply be explained by patient comorbidities. Higher RV/LV-ratio at diagnosis predicted reduced 6MWT results. Unemployment and ongoing anticoagulation predicted impaired HRQoL.